2022
DOI: 10.24298/hedn.2020-0013
|View full text |Cite
|
Sign up to set email alerts
|

Disaster preparedness among foreign residents in a rural area of Japan: A qualitative pilot study

Abstract: Aim: Japan is a particularly disaster-prone country, with natural disasters posing a constant threat to the health and safety of the country's residents. Foreign residents in Japan have been identified as a group considered more vulnerable to disasters occurring in the country. The purpose of this paper is to describe findings from a pilot study exploring knowledge and perspectives related to disaster preparedness among foreign residents in Japan. It also highlights ways that public health nurses can contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 29 publications
0
9
0
Order By: Relevance
“…Older age and the presence of children were associated with higher preparedness (Dasgupta et al, 2020;Green, Linley, Whitney, & Sano, 2021;Nishiyama & Glauberman, 2022). The participants mentioned that their children made disaster kits after learning about them at school (Nishiyama & Glauberman, 2022).…”
Section: Demographicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Older age and the presence of children were associated with higher preparedness (Dasgupta et al, 2020;Green, Linley, Whitney, & Sano, 2021;Nishiyama & Glauberman, 2022). The participants mentioned that their children made disaster kits after learning about them at school (Nishiyama & Glauberman, 2022).…”
Section: Demographicsmentioning
confidence: 99%
“…The proportion of respondents with emergency plans ranged from 9% to 45% (Abukhalaf, von Meding, Dooling, & Abusal, 2022;Bethel, Burke, & Britt, 2013;Carter-Pokras et al, 2007;Nishiyama & Glauberman, 2022). However, Nepal, Banerjee, Perry and Scott (2012) found that most participants lacked adequate emergency plans.…”
Section: Immigrants' Disaster Preparednessmentioning
confidence: 99%
See 3 more Smart Citations